The needs and perceptions of academics regarding their professional development in an era of educational transformation - Hassan , S (South African Journal of Higher Education, 2011)
As the wave of educational transformation sweeps across the higher education landscape, few academics have been unaffected by its impact. It has been well documented that academics are ill-prepared to cope with the challenges of educational transformation, yet training and development that would provide the appropriate support to meet the demands of educational transformation is often neglected. To help address this problem, a study was done to determine the needs and perceptions of academics regarding their professional development within the context of educational transformation. Respondents expressed a need for training in the implementation of innovative methods of teaching and learning such as: outcomes-based education; problem-based learning and technology-enhanced teaching and learning. The article also argues that there is more to educational transformation than meets the eye.